Conditional grants to independent regional governments: The trade-off between incentives and wasteful grant-seeking - Ivo Bischoff; Frédéric Blaeschke (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
The paper addresses the welfare implications of conditional grants in the presence of inefficiencies in regional production. While conditional grants may set incentives for regions to reduce inefficiencies, resources are wasted in the process of grant-seeking. We provide a theoretical model to assess the net effect on welfare. A game-theoretic context is developed to derive the optimal grant-distribution scheme. Depending on the characteristics of the collective good and of the regional government, the optimal ratio of conditional to block grants and the optimal number of recipients vary. The impact of different factors on the optimal grant-distribution scheme is derived.
Keywords: D7; H77; H5; H11; 330; conditional grants; inefficiencies; rent-seeking; fiscal federalism; opportunistic government; Finanzausgleich; Öffentliches Gut; Regionalverwaltung; Standortwettbewerb; Rent Seeking; Opportunismus; Finanzföderalismus; Wohlfahrtseffekt; Theorie